OPTIMIZING OUTCOME IN THE UNIVERSITY-INDUSTRY TECHNOLOGY TRANSFER PROJECTS - Hamed ALAVI; Patrycja HĄBEK (Management Systems in Production Engineering, 2016)
Transferring inventions of academic scientists to private enterprises for the purpose of commercialization is long known as University-Industry (firm) Technology Transfer While the importance of this phenomenon is simultaneously raising in public and private sector, only a part of patented academic inventions succeed in passing the process of commercialization. Despite the fact that formal Technology Transfer process and licencing of patented innovations to third party is the main legal tool for safeguarding rights of academic inventors in commercialization of their inventions, it is not sufficient for transmitting tacit knowledge which is necessary in exploitation of transferred technology. Existence of reciprocal and complementary relations between formal and informal technology transfer process has resulted in formation of different models for university-industry organizational collaboration or even integration where licensee firms keep contact with academic inventors after gaining legal right for commercialization of their patented invention. Current paper argues that despite necessity for patents to legally pass the right of commercialization of an invention, they are not sufficient for complete knowledge transmission in the process of technology transfer. Lack of efficiency of formal mechanism to end the Technology Transfer loop makes an opportunity to create innovative interpersonal and organizational connections among patentee and licensee company. With emphasize on need for further elaboration of informal mechanisms as critical and underappreciated aspect of technology transfer process, article will try to answer the questions of how to optimize knowledge transmission process in the framework of University-Industry Technology Transfer Projects? What is the theoretical basis for university-industry technology transfer process? What are organization collaborative models which can enhance overall performance by improving transmission of knowledge in University- Firm Technology Transfer process?